2012
DOI: 10.4269/ajtmh.2012.11-0047
|View full text |Cite
|
Sign up to set email alerts
|

Compliance, Safety, and Effectiveness of Fixed-Dose Artesunate-Amodiaquine for Presumptive Treatment of Non-Severe Malaria in the Context of Home Management of Malaria in Madagascar

Abstract: Abstract. Home management of malaria is recommended for prompt, effective antimalarial treatment in children less than five years of age. Compliance, safety, and effectiveness of the new fixed-dose artesunate-amodiaquine regimen used to treat suspected malaria were assessed in febrile children enrolled in a 24-month cohort study in two settings in Madagascar. Children with fever were asked to visit community health workers. Presumptive antimalarial treatment was given and further visits were scheduled for foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Adherence was highest for the use of the malaria RDT kit and for compliance with the malaria treatment recommendation. These are in keeping with other studies conducted in similar settings where CHWs used RDT testing to diagnose malaria and administered treatment to under-5 children [17,18]. Recent emphasis on the need for large-scale community health worker programs highlights the recognition of their effect on strengthening health systems and fostering equity in health access [19,20].…”
Section: Discussionsupporting
confidence: 78%
“…Adherence was highest for the use of the malaria RDT kit and for compliance with the malaria treatment recommendation. These are in keeping with other studies conducted in similar settings where CHWs used RDT testing to diagnose malaria and administered treatment to under-5 children [17,18]. Recent emphasis on the need for large-scale community health worker programs highlights the recognition of their effect on strengthening health systems and fostering equity in health access [19,20].…”
Section: Discussionsupporting
confidence: 78%
“…AS-AQ presents the advantage of requiring one intake per day without fatty food while AL is twice per day with fatty food. However, the tolerability, in particular asthenia and gastro-intestinal disorders may impact the effectiveness of the treatment and should be assessed, particularly while used in home management of malaria [ 30 ] or as intermittent preventive therapy in children [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community case management of malaria by CHWs can also reduce overall and malaria-specific under-5 mortality (63,114). With the emergence of rapid diagnostic tests for malaria, studies have shown that CHWs achieved clinical cures in 98% of childhood cases and adherence to medication treatment in 83% of patients (81,99).…”
Section: Reduction Of Mortality In Children Younger Than 5 Years Of Agementioning
confidence: 99%